Mating disruption of Spilonota ocellana and other apple orchard tortricids using a multispecies reservoir dispenser. Issue 4 (3rd July 2014) - Porcel, Mario; Sjöberg, Patrick; Swiergiel, Weronika; Dinwiddie, Robert; Rämert, Birgitta; Tasin, Marco
Abstract BACKGROUND A new mating disruption formulation for population control of a wide range of tortricid pests, including Spilonota ocellana, was tested in Swedish apple orchards during 2012–2013. Owing to the characteristics of the local agricultural landscape, mating disruption was evaluated in isolated orchards rather than through an area‐wide approach. Parameters such as trap shutdown, communication disruption in field cages, damage level and dispenser emission were measured as efficacy indicators. RESULTS The test formulation reduced the catches in monitoring traps for the entire range of the tested species. In field cages, communication between sexes was disrupted for both Adoxophyes orana and Cydia pomonella. The fruit damage caused by leafrollers (including S. ocellana) was reduced by the treatment. The device showed a constant release of all components for the entire flight activity period of these pests. CONCLUSION Single‐orchard experiments showed a significant effect on field populations of the leafroller species complex. While promising, in light of the variability of the result, field scouting may be required to enable practitioners to estimate the density of the pests and avoid possible unexpected attacks. Additional experiments are needed to evaluate the efficacy of the product against C. pomonella. © 2014 Society of Chemical Industry